DEWAN KOMISARIS DAN TRANSPARANSI: TEORI KEAGENAN ATAU TEORI STEWARDSHIP? - Tarmizi Achmad (University of Merdeka Malang, 2012)
This paper examined the impact of the board of commissioners on voluntary disclosures provided by listed firmsin Indonesia for the period of year 2004 to 2010. The board of commissioners were characterized by boardcomposition, board size, board role and board intensity. Voluntary disclosure was proximate by an aggregateddisclosure score of non-mandatory, non-financial and financial information. The results indicated that boardsize, board intensity (number of board meetings), or board role (number of audit committe members) was significantlyand positively related to the extent of voluntary disclosure as predicted by the agency theory, while boardcomposition (number of insiders) was significantly and negatively related to the extent of voluntary disclosure aspredicted by the stewardship theory. The result showed that independent board members did not conduct theirmonitoring function on management effectively. Alternatively, insiders were involved in operating firms activities.This phenomena might be because most firms were owned by family that tended to appoint the board andmanagement team based on the family ties. Hence, using the stewardship theory was more appropriate to analyzethe boards composition than that of using the agency theory.